SOLID SOLUTIONS OF NIOBIUM IN SYNTHETIC TITANITE - Liferovich R.P.; Mitchell R.H. (My University, 2006)
Synthetic (Ca1-xNax)(Ti1-x Nbx)OSiO4 and Ca(Ti1-2x NbxAlx)OSiO4 solid solutions have been prepared for x = 0.1 and 0.2 by ceramic methods and their crystal structure determined by Rietveld analysis. At ambient conditions, the isomorphic capacity of (F,OH)-free titanite is ~0.25 apfu Nb in a single-site scheme of substitution (2VITi4+ ⇌ VIAl3+ + VINb5+) and ~0.22 apfu Nb in a two-site scheme (VIICa2++VITi4+ ⇌ VIINa++VINb5+). All cations located at the VIIX and VIY sites are disordered. Analysis of tetrahedron bond-lengths indicates the absence of Al3+ replacing Si4+ in coordination tetrahedra. All Nb-doped varieties of titanite adopt space group A2/a. Thus, both single-site and complex multivalent schemes of substitution destroy the coherence of the off-centering of chains of octahedra typical of the CaTiOSiO4 end member, resulting in a P21/a → A2/a phase transition. The (Ca1-xNax) (Ti1-xNbx)OSiO4 scheme of substitution incorporates the larger cations at both the VIIX and VIY sites, whereas the Ca(Ti1-2x NbxAlx)OSiO4 scheme involves only VIY-site (Al3+, Nb5+) cations, with a slightly smaller "average" radius. Unit-cell dimensions change insignificantly and vary sympathetically with the change of average radii of the cations in the (Ca1-xNax) (Ti1-xNbx)OSiO4 series and vary insignificantly in the Ca(Ti1-2x NbxAlx)OSiO4 series. Both Nb-doped titanite and pure CaTiOSiO4 consist of distorted polyhedra. The seven-fold coordination polyhedra and octahedra in Nb-doped titanite are slightly less stretched as compared to those in pure CaTiOSiO4. The SiO4 tetrahedron is compressed in Nb-doped titanite as compared to that in the pure CaTiOSiO4. The experimental data obtained suggest that the existence of a titanite analogue with more than 50 mol.% of NaNbOSiO4 end member is unlikely. The solid solution involving the smaller VI(Al,Nb) cations theoretically could be stabilized at high pressure, suggesting the existence of a potentially new species dominated by the Ca(AlNb)OSiO4 end member. The synthetic titanite compositions may be suitable for the sequestration of radioactive waste containing 94Nb.
Keywords: ALUMINUM; CRYSTAL STRUCTURE; DISTORTION; NIOBIUM; RADWASTE DISPOSAL; RIETVELD ANALYSIS; SODIUM; TITANITE